YES/NO QUESTION ON CONVERSATION IMPLICATURE IN ADVERTISING E-COMMERCE - Bambang Prastio; Abdul Syukur Ibrahim; Gatut Susanto; Istiqomah Nurzafira (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
The using of yes/no question is a productive tool for reaching the function of communication discourse. The aimed of this research is testified the function of yes / no question in implicature discourse on e-commerce advertisement. The sources of this research were 8 enterprises advertisement of e – commerce which had variation of e-commerce advertisements. This research is merged the conversation analyses and implicature on conversation. The question yes / no in implicature conversation have different functions, such as: ordering, asking, suggesting, and rejecting.